The legal cultures and Social Changes of ethnic groups : The Case studies of the Lisu Ethnic Group in Wiang Tai and Lahu in Mae Na Toeng ,Pai District ,Mae Hong Son Province - พันธุ์คงชื่น นิล (Community and Social Development Journal, 2018)
Abstract The objectives of this research were to study legal culture of ethnic groups And the change of legal culture society of Lisu ethnic in Wiang Tai and Lahu in Mae Na Toeng ,Pai District ,Mae Hong Son Province ,Thailand. This research use qualitative research methodology. By Documentation and field data collection. Based on interviews with community leaders along with ethnic groups of Lisu ethnic in Wiang Tai and Lahu in Mae Na Toeng ,Pai District ,Mae Hong Son Province ,Thailand. And use interviews with relevant local government officials and descriptive data analysis. According to studies, it has been found that legal culture of Lahu ethnic in Mae Na Toeng ,Pai District ,Mae Hong Son Province ,Thailand. Lahu still have leaders who come from the respect of the people in the community. There is a village director. Due to the large population, traditional traditions are not enough to practice together. There must be a village rule for members to practice. If anyone commits an offense, the village rule will come first, especially the violate custom or fornicate. Legal Culture of Lisu ethnic group, Wiang Tai ,Pai District ,Mae Hong Son Province ,Thailand. There is a change in tradition by the leader of a traditional judiciary. Because they are not living together, only one Lisu ethnic group. However, there are tai-yai ethnic group who have already lived in the area. Therefore, the village rules must be created together. For the peace of the village. But the village rules are not legally enforceable. There are also those who cooperate and who do not follow the rules of the village as well.